Aspects of inter-organisational networks for developing firm competencies - Preliminary evidence from Malaysia - Omar, , Aliza Akmar; Mohan, , Avvari V. (2006)
This paper presents the results of a preliminary study on an inter-organisational network and the development of organisational competencies among a 'flagship cluster' of organisations. The case study involves a consortium of organisations working on a Government Multi Purpose Card (GMPC) project, one of the various Multimedia Super Corridor (MSC) initiatives proposed under the seven flagship applications deployed by the Malaysian Government. The approach has been qualitative and exploratory with data collected via interviews with project partners. While the outcome supports various findings from previous literature on inter-organisational learning networks, further research is needed to test the findings as they result from a single case study. The findings show the benefits to organisations that partake in inter-organisational networks. The benefits are in terms of the different competencies that organisations in emerging economies can gain from their local and foreign partners in the network. This paper puts forward an approach in understanding inter-organisational learning networks from a qualitative and non-experimental perspective, of which only a small of researchers have attempted to do.